Phenomena and POV Reality in Central Java 2017-2023 - Garnis Permata Sari; Purnomo, Didit (Majapahit Journal of Islamic Finance and Management, 2025)
This study investigates the interplay between poverty, open unemployment, and the Gender Development Index (IPG) on regional economic growth in Central Java from 2017 to 2023, using GRDP as the dependent variable across 30 regencies and cities. While the Fixed Effect Model reveals a significant negative effect of open unemployment on GRDP, the findings that poverty and IPG do not show statistical significance should be interpreted with caution. The absence of significance may stem from measurement limitations, temporal lags, or regional heterogeneity rather than a definitive lack of influence. Furthermore, the study acknowledges its limitation in not incorporating broader determinants of economic growth, such as capital investment, infrastructure, human capital, and institutional quality, which could contribute to omitted variable bias. The analysis would benefit from being situated within established economic growth theories, such as Solow’s neoclassical model or endogenous growth frameworks, to better justify variable selection and interpret findings within a broader theoretical and developmental context. Recognizing the long-term contributions of gender equality to economic development, future research should explore the temporal dynamics of IPG’s impact to capture delayed effects often noted in development economics.